2011
DOI: 10.4102/sajip.v37i1.934
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary factor analytic investigation into the firstorder factor structure of the Fifteen Factor Plus (15FQ+) on a sample of Black South African managers

Abstract: Orientation: The Fifteen Factor Questionnaire Plus (15FQ+) is a prominent personality questionnaire that organisations frequently use in personnel selection in South Africa.Research purpose: The primary objective of this study was to undertake a factor analytic investigation of the first-order factor structure of the 15FQ+.Motivation for the study: The construct validity of the 15FQ+, as a measure of personality, is necessary even though it is insufficient to justify its use in personnel selection.Research des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
7
0
2
Order By: Relevance
“…Personality has been identified as cognitive and behavioral patterns that display stability over time and across circumstances (Ranwala and Dissanayake, 2016). Also, personality traits have been identified as important predictors of educational attainment (von Stumm et al, 2011), career success (Stumpp et al, 2010), attitude towards employability, employability skills (Qenani et al, 2014;Nwogu and Momho, 2015;Potgieter, 2012) and job performance (Chamorro-Premuzic and Furnham, 2010;Moyo and Theron, 2011). Nonetheless, little is known about how personality traits affect self-perceived employability.…”
Section: The Importance Of Personality Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Personality has been identified as cognitive and behavioral patterns that display stability over time and across circumstances (Ranwala and Dissanayake, 2016). Also, personality traits have been identified as important predictors of educational attainment (von Stumm et al, 2011), career success (Stumpp et al, 2010), attitude towards employability, employability skills (Qenani et al, 2014;Nwogu and Momho, 2015;Potgieter, 2012) and job performance (Chamorro-Premuzic and Furnham, 2010;Moyo and Theron, 2011). Nonetheless, little is known about how personality traits affect self-perceived employability.…”
Section: The Importance Of Personality Traitsmentioning
confidence: 99%
“…Self-perceived employability is defined as an individual's perception or belief of how easy it is to find new employment (Rothwell and Arnold, 2007). According to Moyo and Theron (2011), self-perceived employability encourages the confidence that a person can be able to secure a job in the labor market, thus promoting the feeling of being in control of one's career.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have related people's personalities to their jobs, contextual performance and characteristic behavioural patterns that distinguish them from others (Moyo & Theron, 2011). Jung (1971) and Myers, McCaulley, Quenk and Hammer (2003) contend that people's natural personality preferences cause them to develop habits of behaviour and personality patterns that characterise their preferred decision-making and problem-solving processes.…”
Section: Trends From the Research Literaturementioning
confidence: 99%
“…Emotional intelligence has been recognised as a career metacapacity which influences people's employability and career success (Coetzee & Beukes, 2010;Emmerling & Cherniss, 2003;Poon, 2003). Individuals' emotional intelligence has been related to their job and contextual performance and characteristic behavioural patterns which distinguish them from others (Moyo & Theron, 2011). Brown, George-Curran, and Smith (2003) found that when people possess a high level of emotional intelligence, they are more likely to achieve career success and perform well in career-related tasks (which could include higher employability skills).…”
Section: Emotional Intellegence In the Career Contextmentioning
confidence: 99%